2000
DOI: 10.1016/s0886-3350(00)00468-5
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse lamellar keratitis: Diagnosis and management

Abstract: With the volume of laser in situ keratomileusis procedures growing exponentially, ophthalmologists and other eye-care providers are becoming aware of an uncommon postoperative condition, diffuse lamellar keratitis, that can affect an otherwise ideal outcome. We present our strategy for diagnosing and managing this syndrome, developed from experience in a high-volume refractive surgical practice. Understanding the time course of the disease, along with proper identification, staging, and intervention, can help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
142
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(150 citation statements)
references
References 5 publications
0
142
0
8
Order By: Relevance
“…However, in most cases, especially in epidemic DLK, it has been associated to the presence of bacterial endotoxins (2,8,9) , meibomian glandular secretions and peripherals immune infiltrates, atopy, iatrogenic epithelial defects or resulting from problems during the process of sterilization of instruments, related for example to gloves and surgical marking pens. Finally, DLK is probably the result of endogenous risk factors of the patient in response to exogenous exposure (10) , though isolated cases of idiopathic DLK have also been sporadically observed (11) . However, if many cases happen in a short period of time, precautions should be taken to assess sterilization process (2,8) .…”
Section: Diffuse Lamellar Keratitis (Dlk) or Sands Of The Sahara Syndmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in most cases, especially in epidemic DLK, it has been associated to the presence of bacterial endotoxins (2,8,9) , meibomian glandular secretions and peripherals immune infiltrates, atopy, iatrogenic epithelial defects or resulting from problems during the process of sterilization of instruments, related for example to gloves and surgical marking pens. Finally, DLK is probably the result of endogenous risk factors of the patient in response to exogenous exposure (10) , though isolated cases of idiopathic DLK have also been sporadically observed (11) . However, if many cases happen in a short period of time, precautions should be taken to assess sterilization process (2,8) .…”
Section: Diffuse Lamellar Keratitis (Dlk) or Sands Of The Sahara Syndmentioning
confidence: 99%
“…According to Linebarger, DLK is divided into four phases according to its clinical presentation (10) : Diffuse lamellar keratitis seems to be slightly more common with the use of femtosecond laser compared to the microkeratome for making the flap. Studies have shown that high levels of laser energy result in tissue injury induced by photodisruption, causing accumulation of gas bubbles which may lead to an increased inflammatory response of DLK.…”
Section: Diffuse Lamellar Keratitis (Dlk) or Sands Of The Sahara Syndmentioning
confidence: 99%
See 2 more Smart Citations
“…24,88,89 Postoperative complications include dislodging of the flap, flap striae, interface debris, epithelial downgrowth, and diffuse lamellar keratitis. 24,90,91 Posterior segment complications, such as posterior vitreous detachment, [92][93][94] Clinical Optometry downloaded from https://www.dovepress.com/ by 54.191.190.102 on 13-May-2018 For personal use only.…”
Section: Complicationsmentioning
confidence: 99%